Supramolecular cages as differential sensors for dicarboxylate anions: guest length sensing using principal component analysis of ESI-MS and 1H-NMR raw data. Issue 12 (15th February 2019) - Bravin, Carlo; Guidetti, Andrea; Licini, Giulia; Zonta, Cristiano
Abstract : A differential sensor based on cages discriminate guests according to their length. Abstract : Dynamic covalent libraries (DCLs) have been widely used in the development of differential sensors. Inspired by recent studies which use supramolecular recognition systems for sensing, we report the use of a tris(-pyridylmethyl)amine (TPMA)-based supramolecular cage as a differential sensor for dicarboxylate anions. In particular, a library of molecular cages constituted by linkers differing in size and flexibility was allowed to equilibrate toward a series of guests differing in molecular size. The differential system was able to discriminate a series of dicarboxylates depending on their chain length. This differentiation was evaluated through the application of the Principal Component Analysis (PCA) method using interpolated and raw data obtained from ESI-MS. Interestingly, while the 1 H NMR spectra of the differential system did not allow for the discrimination of the analytes by the naked eye, PCA of the raw data from the spectra revealed information on the chain length of the guest and also on the odd-even character of the carbon chain.